Edukasi Deteksi Dini Stroke dengan Media Berbasis Audio Visual Pada Komunitas Diabetes dan Hipertensi Pada Masa Pandemi Covid-19 - Mike Asmaria; Hilma Yessi; Hidayati Hidayati (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Many factors accelerate the incidence of diabetes and hypertension, getting taller the level of sugar in the blood, the easier it is to have a stroke. Uncontrolled hypertension is one of the most risk factors for stroke incidence. Health problems that cause disability and death are still high, this is probably due to community habits that are difficult to change, such as food and drink consumption. This community service method is carried out by counseling through audio-visual-based media in the form of video. The results of this community service showed an increase in participants' knowledge from 19.23% to 84.61%. This increase in knowledge was supported by the role of cadres who tried to guide participants with educational videos. It is necessary to maintain knowledge in order to increase awareness of the diabetes and hypertension community in Pauh Barat Village in preventing stroke by following innovations in healthy eating patterns, carrying out regular physical activities and managing stress and emotions well.